Retrieval features for online databases: common, unique, and expected - Othman, Roslina; Halim, Nor Sahlawaty (Emerald Group Publishing Limited, 2004)
The aims of this study were to identify the retrieval features for online databases; difficulties faced by users; and retrieval features expected by users. A total of 25 databases were surveyed and 40 users were interviewed after the training sessions. Common retrieval features included Boolean operators,phrase searching, match of exact words or phrases, field specific and limit fields searches, truncation, and wildcard. Even though features are offered in many systems, their interpretation andimplementation are different. Unique features included lateral searching, density and frequency of terms, reference link, and searching via table of content. The expected features includedrelevance feedback and term weighting other than those already offered by ACM Digital Library and IEEE Xplore. Such expectations were influenced by the users’ background in ICT. Difficulties included application of the retrieval features in searching. Database providers must include the expected features, synonyms linked to terms in the thesaurus, and extensive search examples.